Educação Profissional e Tecnológica: análise dos regulamentos dos Núcleos de Apoio às Pessoas com Necessidades Educacionais Específicas dos Institutos Federais da Região Sudeste - Silva, Jussara Cristina Rodrigues da (2023)
With the expansion of the Federal Network of Professional and Technological Education, the number of students enrolled increased and, consequently, the diversity of students within these training spaces. Due to the significant growth in the number of enrollments of students who are the target audience of Special Education – PAEE in Professional Education and with the requirement to comply with the current legislation on inclusion, the Federal Institutes, through the TEC NEP Program, implemented the Support Centers for People with Specific Educational Needs – NAPNEs with the objective of promoting actions related to admission, the permanence and success of PAEE students. In this context, the interest arose in carrying out the present research, which had as its general objective: to understand how the Inclusion Policy in the Federal Network of Professional, Scientific and Technological Education is configured, from the analysis of the regulations of the NAPNEs of the Federal Institutes of Education, Science and Technology of the Southeast Region of Brazil. The specific objectives of the research were: to present the constituent elements of the NAPNEs of the Southeast Region; identify the common core of the proposition of the NAPPE regulations; reflect on the meanings that the common core of the NAPNEs regulations can assume in the Inclusion Policy of the Federal Institutes of the Southeast Region; to verify how the different discursive processes of the NAPNEs regulations are associated and how this expresses a Policy of Inclusion in Professional, Scientific and Technological Education. In order to verify how the inclusion policy is being appropriated and translated into the documents that guide its implementation in the contexts of the Federal Institutes of the Southeast Region of Brazil, we chose documentary research as a methodological procedure for the development of the research. The sources used were the regulations of the NAPNEs or equivalent sectors of the Federal Institutes of the Southeast Region of Brazil. For this study, two chapters were elaborated. The first deals with the bibliographic review on the theme of inclusion in the Federal Network of Professional and Technological Education, in which we rescue some historical elements of the process of construction of this Network in Brazil, followed by the survey of the main milestones of the process of implementation and implementation of the Inclusion Policy in the referred Network. And the second chapter refers to the presentation and discussion of the results of the research carried out with the regulations of the NAPNEs of the Southeast Region of Brazil. Incorporating elements of discourse analysis, the methodological path made it possible to identify that the common core, present in the proposition of the documents, is constituted by the concepts Education – Work – Disability, concepts that permeate the entire analytical discussion of the analyzed regulations and that, by establishing a relationship between them, express a contradictory Inclusion Policy in Professional and Technological Education. This policy is marked, on the one hand, by an education conceived as a driving force for the development of productive skills for capital, manifesting itself above all in the conception of success materialized in the insertion of PAEE students in the labor market. And on the other hand, it is marked by an education that establishes, as one of its fundamental principles, the development of human capacities, in the sense of the integral formation of these same students.